PENGUATAN MINAT BELAJAR BAHASA INGGRIS MELALUI KEGIATAN ENGLISH CAMP - Akib, Rizal; Uluelang, Kris; Saputra, Dian; Wael, Ahmad (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
As an effort to promote students' interest in improving speaking and communicating skills in English, it is necessary to implement a community service program that can help them get started. This time the service held an English Camp activity at SMA Negeri 13 with the workshop method of providing material, Discussion Group Assistance and English Games for two consecutive days. This service activity begins by dividing the participants into small groups accompanied by student instructors. The results of this service received a positive response from the participants, this response showed students' interest in improving their skills in English, especially intensive English learning activities involving games which increased the participants' vocabulary mastery.